Low Temperature Infrared Spectroscopy Study of Pyrazinamide: from the Isolated Monomer to the Stable Low Temperature Crystalline Phase - Borba, Ana (2010)
A structural and spectroscopic analysis of the anti-tuberculosis drug pyrazinamide (PZA) was carried out. The PZA molecule was predicted theoretically to possess two conformers differing by internal rotation around the C - C(=O) bond, with the E conformer (Cs symmetry point group; N - C - C=O dihedral: 180°) being ca. 30 kJ mol-1 more stable than the Z form (C 1 point group; N - C - C=O dihedral: ca. ± 42°). In consonance with both the large energy difference and low energy barrier between the Z and E conformers, upon isolation in low temperature argon and xenon matrices, only the E form could be observed and characterized spectroscopically. In the argon matrix, this conformer was found to exist in at least three matrix sites, of different stability. In a supersonic jet, besides the monomer (E), the most stable dimer of PZA with two equivalent NH O= hydrogen bonds could also be identified. Its spectrum reveals rapid energy flow out of the excited NH stretching mode mediated by one of the heteroatoms in the ring. Finally, the IR spectra of the amorphous solid resulting from fast cooling of the vapor of the compound (initially in the a crystalline phase) onto the cold substrate of the cryostat (10 K) and of the crystalline phase resulting from warming the amorphous solid were also recorded and interpreted. The obtained crystalline phase was found to be the thermodynamically most stable δ polymorph of PZA.